2013
DOI: 10.1088/0957-4484/24/27/275606
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled Al nanoparticles on Si and fused silica, and their application for Si solar cells

Abstract: This paper presents a novel method for the self-assembly of aluminum nanoparticles on Si and fused silica. Due to high reactivity with oxygen, ex-vacuo annealing of thin deposited metal films, a method used extensively with other metals, does not work with aluminum. In the present experiment this problem was overcome by annealing the samples in-vacuo in the deposition chamber. Aluminum was thermally evaporated onto substrates at elevated temperatures (200-400 ° C) and annealed for 60 min without breaking the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Metallic NPs can demonstrate increased light absorption and emission owing to the localized surface plasmon resonance (LSPR) [13], and their optical properties can efficiently be tuned by the control of shape, size, and density of NPs [46]. Silicon is one of the most abundant semiconductor materials widely utilized for photovoltaic solar cells and photodetectors [710], and the performance of Si-based optoelectronic devices can be significantly improved by the integration of metallic NPs [1116]. For instance, self-assembled aluminum (Al) NPs fabricated on Si can enhance the efficiency of solar cells owing to the LSPR exhibited by Al NPs [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallic NPs can demonstrate increased light absorption and emission owing to the localized surface plasmon resonance (LSPR) [13], and their optical properties can efficiently be tuned by the control of shape, size, and density of NPs [46]. Silicon is one of the most abundant semiconductor materials widely utilized for photovoltaic solar cells and photodetectors [710], and the performance of Si-based optoelectronic devices can be significantly improved by the integration of metallic NPs [1116]. For instance, self-assembled aluminum (Al) NPs fabricated on Si can enhance the efficiency of solar cells owing to the LSPR exhibited by Al NPs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is one of the most abundant semiconductor materials widely utilized for photovoltaic solar cells and photodetectors [710], and the performance of Si-based optoelectronic devices can be significantly improved by the integration of metallic NPs [1116]. For instance, self-assembled aluminum (Al) NPs fabricated on Si can enhance the efficiency of solar cells owing to the LSPR exhibited by Al NPs [11]. Similarly, Si-based LEDs can produce a superior light emission via the excitation of surface plasmon resonance by silver (Ag) NPs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Al nanostructures support localized plasmon resonances in the ultraviolet (UV) and visible region of the spectrum and they could be used as substrate for metal-enhanced fluorescence, UV-SERS, or for enhancing the efficiency of optoelectronic devices [30][31][32][33][34][35].…”
Section: Page 4 Of 21mentioning
confidence: 99%
“…This is why most works have previously focused on red-shifting the LSPRs into the near-IR region to increase light absorption in that region, as explained in the introduction. However, Villesen et al 27 showed experimentally that there is photocurrent enhancement only at frequencies lower than the the main LSPR frequency (i.e., longer wavelengths). Hence the bluer LSPR positions of the Al MNPs allow enhancement to occur over a larger portion of the solar spectrum as opposed to Ag MNPs.…”
Section: Effect Of Mnp Materials On Plasmonic Enhancementmentioning
confidence: 99%